Development of an Android-Based Expert System for Diagnosing Cat Skin Diseases at Cat’s Petshop Depok Using the Certainty Factor Method with Android Studio and MySQL - Putriningsih, Prastika; Faizah, NM; Nurcahyo, Widyat (Journal Mobile Technologies (JMS), 2024)
Limited understanding among cat owners regarding skin diseases in cats can have significant implications for the well-being of both cats and humans in the future. Certain skin conditions in cats are not confined to the animals themselves but can be transmitted to humans and other animals. To address such challenges, the development of an expert system for diagnosing skin diseases in cats is proposed. The study was conducted at Cat’s Petshop and Animal Clinic in Grand Depok City. Data were gathered through interviews with Drh. Atiek and Drh. Zeta, veterinarians at the location. The interviews identified six prevalent types of skin diseases in cats. Key issues include the manual recording system at the clinic, lengthy examination queues due to veterinarians’ packed schedules, and the limited knowledge of pet owners regarding symptoms of skin diseases in cats, which delays the diagnostic process. A solution was implemented by designing an expert system for diagnosing skin diseases in cats using the certainty factor method, which quantifies the confidence level of experts in their diagnoses. The application assists cat owners in identifying the type of skin condition affecting their pets. The certainty factor method enhances accuracy by accounting for uncertainty in calculations. The expert system yields positive outcomes. Primarily, it accelerates the examination of skin diseases in cats at Cat’s Petshop Depok. Additionally, it improves the precision of preliminary diagnoses. The deployment of the application saves time for pet owners and reduces waiting times at the clinic. The diagnostic accuracy aligns with the certainty factor calculation approach, addressing uncertainties in results. Overall, the expert system employing the certainty factor method offers an effective solution to overcome the lack of understanding among cat owners about skin diseases. The application facilitates early symptom recognition, enhances time efficiency, and improves diagnostic precision.